1999
DOI: 10.1289/ehp.99107s5793
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to crystalline silica and autoimmune disease.

Abstract: Occupational exposure to silica dust has been examined as a possible risk factor with respect to several systemic autoimmune diseases, including scleroderma, rheumatoid arthritis, systemic lupus erythematosus, and some of the small vessel vasculitidies with renal involvement (e.g., Wegener granulomatosis). Crystalline silica, or quartz, is an abundant mineral found in sand, rock, and soil. High-level exposure to respirable silica dust can cause chronic inflammation and fibrosis in the lung and other organs. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
2
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(118 citation statements)
references
References 91 publications
4
108
2
4
Order By: Relevance
“…A similar mode of action has been suggested for silica. 21 In a previous publication, we presented results from a casereferent study of occupational determinants which both corroborated previous reports and indicated new relationships. 14 In order to further explore the impact of occupational exposures, a second case-referent study with prospective inclusion of cases has now been performed.…”
supporting
confidence: 87%
“…A similar mode of action has been suggested for silica. 21 In a previous publication, we presented results from a casereferent study of occupational determinants which both corroborated previous reports and indicated new relationships. 14 In order to further explore the impact of occupational exposures, a second case-referent study with prospective inclusion of cases has now been performed.…”
supporting
confidence: 87%
“…60 In our analysis, although only two silicotics had systemic sclerosis, the MOR of 2.0 (95% CI 0.4 to 10.3) is suggestive of an association. However, the evidence for an association between this disease and crystalline silica exposure is equivocal.…”
Section: Systemic Sclerosismentioning
confidence: 47%
“…59 Some of these mechanisms have been postulated to explain the role of crystalline silica exposure in autoimmune disease. 60 …”
Section: Autoimmune Related Diseasesmentioning
confidence: 99%
“…It has previously been proposed that increased release of inflammatory mediators from alveolar macrophages phagocytosing inhaled silica particles may activate macrophages/monocytes and lymphocytes systemically as well as in the rheumatoid synovium. [19][20][21][22][23][24][25] These cell types also have the potential to increase the production of matrix metalloproteinases (MMP)-enzymes involved in the degradation and remodelling of extracellular matrix, which have been shown to be associated with rheumatoid arthritis as well as with silicosis. [26][27][28][29] The production of MMP, as well as of inflammatory mediators such as tumour necrosis factor a and interleukin 1b, is regulated by the transcription factor nuclear factor kB, the activity of which appears to be influenced by silica exposure.…”
Section: Discussionmentioning
confidence: 99%